The Impact of Digital Education Skills on Basic School Teachers from Their Perspective in Irbid Governorate - Majdoleen Hamdi Mahmoud Mansour; Ashraf Ali Bani Yassin (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
This study aimed at identifying the effectiveness of digital education skills for basic school teachers in Irbid Governorate from their point of view. The study sample consisted of (112) male and female basic school teachers in the Northern Mazar District Directorate in Irbid Governorate, they were chosen randomly. The researchers used a questionnaire specially prepared for the purposes of this study, where the study was implemented in the academic year 2021/2022. The results showed that the effectiveness of digital education skills for basic school teachers in Irbid governorate from their point of view came to a high degree, with an arithmetic mean (3.80) and a standard deviation (0.29). The study also resulted in the absence of statistically significant differences between the views of the study sample due to gender variables. The study recommended working on developing educational platforms and technological tools, developing educational software, increasing the necessary technical and logistical support, and training them on how to practice them in the classroom.